Shattered pellet injection experiments at JET in support of the ITER disruption mitigation system design. (21st December 2021) - Jachmich, S.; Kruezi, U.; Lehnen, M.; Baruzzo, M.; Baylor, L.R.; Carnevale, D.; Craven, D.; Eidietis, N.W.; Ficker, O.; Gebhart, T.E.; Gerasimov, S.; Herfindal, J.L.; et al.
Abstract: A series of experiments have been executed at JET to assess the efficacy of the newly installed shattered pellet injection (SPI) system in mitigating the effects of disruptions. Issues, important for the ITER disruption mitigation system, such as thermal load mitigation, avoidance of runaway electron (RE) formation, radiation asymmetries during thermal quench mitigation, electromagnetic load control and RE energy dissipation have been addressed over a large parameter range. The efficiency of the mitigation has been examined for the various SPI injection strategies. The paper summarises the results from these JET SPI experiments and discusses their implications for the ITER disruption mitigation scheme.